The effect of vitamin D supplementation on gestational diabetes in high-risk women: Results from a randomized placebo-controlled trial - Shahgheibi, Shole (J Res Med Sci, 2016)
BACKGROUND: Vitamin D deficiency is common in pregnancy, leading to increase in the frequency of preeclampsia, cesarean delivery, neonatal bacterial vaginosis, and gestational diabetes. The current study was designed and implemented to investigate the effect of vitamin D during the first and second trimesters of pregnancy in reducing the risk of gestational diabetes mellitus (GDM) in women who are at high risk [history of GDM, birth macrosomia, family history, and high body mass index (BMI)]. MATERIALS AND METHODS: In a randomized, double-blind, and placebo-controlled trial, 90 pregnant women who had at least one risk factor for GDM were randomized into intervention (46 participants) and control (44 participants) groups. Participants in the intervention group took 5000 units of vitamin D daily and the control group took placebo until the 26th week of pregnancy. Then the glucose challenge test (GCT) and the glucose tolerance test (GTT) were performed to evaluate GDM. RESULTS: Mean ± standard deviation (SD) age was 31.28 ± 6.38 years and 29 ± 6.24 years for the intervention group and the placebo group, respectively, (P > 0.05). In addition, there were no significant differences between two groups in terms of vitamin D levels and GCT (P > 0.05), and the difference was not significant. The incidence of diabetes in the intervention groups was statistically lower than in control group (11.4% vs 34.8; P < 0.01). The results showed that abnormal GCT in the placebo group was statistically higher than in intervention group (35.9% vs 10.9 P < 0.005). CONCLUSION: The results of the current study showed that the prescription of vitamin D supplementation in the first and second trimesters of pregnancy was effective in reducing GDM and controlling GTT and GTC.